PERAN MEDIA SOSIAL TWITTER TERHADAP BRAND AWARENESS PADA PERUSAHAAN PENERBANGAN INDONESIA - M. Ridwan; Sigit Tri Antoro; Imam Ozali (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The objective of this research is to find out the role of social media Twitter toward brand awareness on Indonesian airlines. Research methodology used was regression analysis techniques, coefficient correlation, coefficient determinant, and hypothesis testing.   The result of the analysis and discussion shows positive correlation between social media Twitter toward brand awareness shown by simple linear regression equation Y = 7.565 + 0.516X.  The role of social media Twitter toward brand awareness is strong since the correlation coefficient (r) equals to 0.604. Coefficient determinant equals to 36.3% which means contribution of X variable (social media Twitter) toward the fluctuation of Y variable (brand awareness) is 36.3%.  The result of hypothesis testing shows that tstat > ttable (6.938 > 1.988).  There is a significant role of social media Twitter toward brand awareness.